2023
DOI: 10.1002/cbdv.202201176
|View full text |Cite
|
Sign up to set email alerts
|

Activating Blood Circulation, Anti‐Inflammatory and Diuretic Effects of Leonurus japonicus Extract on a Rat Model of Trauma Blood Stasis and Its Phytochemical Profiling

Abstract: Leonurus japonicus Houtt. has been traditionally used to treat many ailments. This study evaluated the activating blood circulation, anti-inflammatory, and diuretic effects of L. japonicus extract (LJ) and identified its phytochemicals. In this work, the phytochemicals in LJ were identified using liquid chromatography mass spectrometry. Rats were randomly assigned to three groups (n = 8): Control group was treated with saline, while the Model group (saline) and LJ group (426 mg/kg) had induced traumatic injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Leonurus japonicus is a plant worldwide used by the population to treat different health problems. [14,15,23,26,27] Previous studies of its use as an anti-inflammatory can be found in the scientific literature; [19,28] however, its usage for wound healing is slightly related. [29] In several extracts of Leonurus species, different secondary metabolites are present, the flavonoids being the main metabolites (e. g. flavonoids such as quercetin and derivatives).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Leonurus japonicus is a plant worldwide used by the population to treat different health problems. [14,15,23,26,27] Previous studies of its use as an anti-inflammatory can be found in the scientific literature; [19,28] however, its usage for wound healing is slightly related. [29] In several extracts of Leonurus species, different secondary metabolites are present, the flavonoids being the main metabolites (e. g. flavonoids such as quercetin and derivatives).…”
Section: Discussionmentioning
confidence: 99%
“…The wound areas (mm 2 ) were registered on the 7th, 14th, and 21st postoperative days and measured using Image J software. [19] The wound contraction was calculated using equation 01; WAi is the initial wound area, and WAf is the wound area after the postoperative days, respectively.…”
Section: Wound Area Measurementsmentioning
confidence: 99%
See 2 more Smart Citations